Herdís & Ólína: The Poetry of Everyday Life - Driscoll, M. J. (Scandinavistica Vilnensis, 2019)
The twin sisters Herdís Andrésdóttir and Ólína Andrésdóttir were born on the island Flatey in Breiðafjörður, western Iceland, in 1858. Following the death of their father at sea three years later, the family was dispersed and the sisters did not see each other until half a century later, when they were reunited in Reykjavík. In the intervening years both sisters had become well known as capable verse-makers in the traditional style, but it had never, it seems, occurred to them to write any of their poems down, let alone publish them. They were encouraged by friends to do so, and in 1924 they brought out a collection of their verse, entitled simply Ljóðmæli (Poems). Their poetry was highly traditional both in its form, which principally made use of rímur and ballad metres, and in terms of its subject matter, dealing with nature, reflections on life’s joys and sorrows and so on. Ólína, like her cousin Theodóra Thoroddsen, also contributed to the revival of the þula, a form of poetry traditionally associated with children. The book sold well, and a second edition, with some additional poems, came out in 1930. A third edition was brought out in 1976, long after their deaths, containing much new material; this edition has since been reprinted twice. Critical reception was overwhelmingly favourable, both in the learned and more popular press. Though somewhat at odds with the literary establishment of the day, they nevertheless had several powerful supporters among the literary and intellectual élite, foremost among them professor Sigurður Nordal. Despite having been “world-famous in Iceland” in their old age, Herdís and Ólína are little known today, and their work – much of it very fine indeed – has yet to receive the scholarly attention it deserves.
Keywords: Icelandic literature; popular poetry; women’s poetry; female authorship; þulur